Effect of hypertension on the progression of chronic renal failure in children - Soergel, Marianne; Schaefer, Franz (American journal of hypertension, 2002)
This article reviews the current state of knowledge concerning the vicious cycle of hypertension and progressive loss of renal function in renal disease, as well as the renoprotective potential of antihypertensive treatment, with a specific focus on children and adolescents.
Gesehen am 02.12.2020